Penyerapan Kosakata Bahasa Daerah ke dalam Bahasa Indonesia pada Kamus Besar Bahasa Indonesia Edisi Keempat - Adi Budiwiyanto (Balai Bahasa Nusa Tenggara Barat, 2009)
Multicultural and multilingual situation in Indonesia lead to language contact that allows borrowing among the languages. The borrowing of local languages, especially the cultural vocabulary, needs to be encouraged in Indonesia language development since the local languages are ‘seedlings’ for the Indonesian vocabulary. Moreover, the rapid growth of science and technology needs to be balanced with the growth of words or terms. This paper discusses the contribution of the local languages in Indonesia to Indonesian vocabulary, especially in the Indonesian Comprehensive Dictionary, the Fourth Edition. Besides, the domain of the words borrowed and the changes occurred, either the form or the meaning, are discussed as well.